The Role of English Proficiency and Financial Development in Stimulating Economic Growth - Shaharuddin, Norhasimah; Abdul Wahab, Mohd Hafiz; Safian, Sharulshahida Shakrien; Osman, Adibah Alawiah (Journal of Entrepreneurship, Business and Economics; Vol 10 No 2S2 (2022): Theme: Digitalization Progress in Business Practices, 2022)
The role of English as the language of trade, finance and technology, has become more vital for development strategies in the 21st century. Recognition of English as the language of communication at the international level not only as knowledge of the language but also the ability to communicate effectively. Thus, the English language has become a necessity to strengthen relations with other countries in the world, especially in international trade, economic development, and financial development. With this motivation, the main purpose of this study was to look the impact of English proficiency in the relationship between financial development and economic growth. Using panel data for 55 countries from 2010-2019, this study applied the generalized method of moments estimation (GMMs). The findings prove that the interaction between English proficiency and financial development has positive impact on economic growth in selected countries. This study suggests that in achieving high and competitive economic growth in this era of globalization, the role of interaction between financial development and English Language Proficiency is vital to consider a reform that would strengthen the financial development and stimulate economic growth as well as development. Research paper Keywords: English Language Proficiency, Financial Development, Economic Growth, GMMs Reference to this paper should be made as follows: Shaharuddin, N., Abdul Wahab, M. H., Safian, S. S., & Osman, A. A. (2022). The Role of English Proficiency and Financial Development in Stimulating Economic Growth. Journal of Entrepreneurship, Business and Economics , 10 (2S2), 18–37.